Developing an Understanding for Wastewater Treatment in Remote Communities in Nunavut, Canada: Investigating the Performance, Planning Practice and Function of Tundra and Constructed Treatment Wetlands - Yates, Colin Nathan (University of Waterloo, 2012)
Since humans began to permanently settle locations for extended periods of time there has been the challenge to safely dispose of, or treat human effluent. In specific to the communities of Nunavut and Arctic Canada, the treatment of wastewater has been particularly challenging. The harsh climate, remote nature and socio-economic factors are a few of the aspects which make the treatment of wastewater problematic in Canadian Arctic communities. In the past several decades a number of conventional and alternative wastewater treatment systems (e.g. lagoons and tundra wetlands) have been proposed and implemented in Nunavut and other remote Arctic communities. Knowledge of performance of these systems is limited, as little research has been conducted and regulatory monitoring has been poorly documented or not observed at all. Also, in the past, the rational design process of treatment systems in Arctic communities has not acknowledged cultural and socio-economic aspects, which are important for the long-term management and performance of the treatment facilities in Arctic communities. From 2008 to 2010 I characterized and studied the performance of several tundra wastewater treatment wetlands in the Kivalliq Region of Nunavut, as well as two in the Inuvaliat Region of the Northwest Territories. Performance testing occurred weekly throughout the summer of 2008. Characterization included surveys of plant communities in the tundra wetlands, specifically analyzing the relationship between Carex aquatilis and various nutrient contaminants in wastewater. Through their characterization I was able to provide greater insight into primary treatment zones within the wetland, and identify the main potential mechanisms for the treatment wastewater in the Arctic. I also studied the performance of a horizontal subsurface flow (HSSF) constructed wetland in Baker Lake Nunavut; the first system of its kind in the Canadian Arctic. The weekly performance study showed average weekly percent reduction in all parameters, with small ...